STRATEGI HUMAS DALAM MEMBANGUN REPUTASI LEMBAGA PENDIDIKAN DI ERA SOCIETY 5.0 - Usi Elistatia; Vera Astuti; Romlah; Ali Abdul Wakhid (re-JIEM (Research Journal of Islamic Education Management), 2025)
The era of Society 5.0 requires educational institutions to integrate intelligent technology with human-centered values. This study analyzes the Public Relations strategy of SMP PGRI 2 Bandar Lampung in building the school’s reputation amid rapid digital change. A qualitative case study approach was used through in-depth interviews and observations of online and offline communication activities. Data were analyzed inductively and validated through source and method triangulation. The findings show that the school implements a Symmetrical Digital Transformation Strategy consisting of Reputation Building, which strengthens digital narratives and internal relations, and Issue Management, which emphasizes two-way communication and accurate handling of misinformation. This strategy enhances public trust and community participation, although challenges remain regarding digital literacy gaps. The study highlights the importance of balancing technology, human values, and digital leadership in developing a sustainable reputation.